The SOUDAN 2 detector - The design and construction of the tracking calorimeter modules - Allison, W; Alner, G; Ambats, I; Ayres, D; Balka, L; Barr, G; Barrett, W; Benjamin, D; Bode, C; Border, P; Brooks, C; Cobb, J; et al. (1996)
SOUDAN 2 is a 960-ton tracking calorimeter which has been constructed to search for nucleon decay and other phenomena. The full detector consists of 224 calorimeter modules each weighing 4.3 tons. The design and construction of the modules are described. The modules consist of finely segmented iron instrumented with 1 m long drift tubes of 15 mm internal diameter. The tubes enable three spatial coordinates and dE/dx to be recorded for charged particles traversing the tubes.